Cycle, physicochemical characterization and climatic adaptation of a white hybrid grape on different rootstocks - Mattar, Gabriel Stefanini; Modesto, Lenon Romano; Hernandes, Jose Luiz; Tecchio, Marco Antonio [UNESP]; Moura, Mara Fernandes (Inst Agronomico, 2019)
This study evaluated the cycle duration, physicochemical characteristics of fruits and climatic adaptation of the 'SR 501-17' hybrid grape grafted on four rootstocks for the production of white wine. We tested four rootstocks, 'IAC 766 Campinas', 'IAC 572 Jales', 'IAC 571-6 Jundiai' and 'IAC 313 Tropical', planted in two climatic regions, Cfa and Aw, in the state of Sao Paulo, Brazil in the cultivation years 2014 and 2015. Cycle duration, production, cluster weight, number of berries per bunch, content of soluble solids, titratable acidity, a maturation index and the weight, length and width of berries were evaluated. A principal component analysis characterized the cultivar for both climatic regions and years. The rootstock did not influence the cycle, production or physicochemical characteristics of the 'SR 501-17' hybrid. The soluble-solid content in the must was higher and the production cycle in 2014 was longer for the Cfa climate. The production cycle was shorter and the weight and width of the berries were lower, mainly in 2015, for the Aw climate. The cycle was thus longer, production was higher and the chemical characteristics were better for the 'SR 501-17' hybrid under Cfa conditions, regardless of the rootstock.
Keywords: canopy/rootstock; climate; principal component analysis; Vitis